Study of the Properties of Liquid Light Concrete with Disperse Reinforced with Glass Fiber - Kh., Kuldashev (European Journal of Life Safety and Stability (2660-9630), 2022)
The article describes the experiments and results obtained on the dispersed reinforcement of fine-grained lightweight concrete with fiberglass, as well as the areas of application of such concretes.